Corporate restructuring & downsizing: theories, science, and lessons - De Meuse, Kenneth P. (Henry Stewart Talks, 2014)
Reorganizing, Business advantages, Employee concerns, Layoff survivor syndrome, Employee emotions – Organizational consequences, Merger syndrome, Robino and De Meuse study, Corporate judo, Kubler-Ross model of grieving, Grieving (healing) process: stages, Saturation effect, Series of strategic events, Transitional renewal, Organizational implications – Mnemonic: PROACTIVE, Individual implications